EFEKTIVITAS METODE PEMBELAJARAN ONLINE PADA MASA PANDEMI COVID-19 - Ismiyarti, Wilia; Hudaya, Chairul; Rodianto (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
The spread of COVID-19 has had an impact on all sectors of life, one of which is the education sector. The teaching and learning process which was originally carried out face to face is now switching to online learning. The purpose of this study was to determine how effective the online learning method was during the COVID-19 pandemic at a private university. There are 3 methods in this research, namely synchronous, asynchronous and mixed learning methods with the nature of the research is quantitative. Data collection techniques were carried out by distributing questionnaires in the form of google form to 100 students and 60 lecturers as respondents. The results of research on student respondents showed that mixed online learning methods were very effective during the covid-19 pandemic with an effectiveness ratio value of 81 and a percentage of 34%. while the synchronous and asynchronous methods are quite effective with the percentages of 32% and 33%, respectively. However, lecturer respondents indicated that the three methods were quite effective with the percentage of synchronous learning 32%, asynchronous and mixed learning 34% each.